Prototype Alat Pendeteksi Banjir Berbasis Internet of Thing Terintegrasi Aplikasi Instant Messanging - Asep Marzuki; Afifah Cahayani Adha (Universitas Harapan Bangsa, 2024)
Indonesia is a tropical country that has two seasons, namely summer and rainy season. The weather in Indonesia is currently erratic, it is influenced by changes in extreme weather in the world. These extreme weather changes cause the public to be aware of disasters that can occur at any time. This change in weather triggers a prolonged rainy season or vice versa. During the legal season in Indonesia, many areas are affected by floods. Throughout 2021 BNPB recorded 1,298 flood disasters. When a flood disaster occurs, protection of houses is rarely carried out, this is due to the absence of early warning to the public, so that the occurrence of floods cannot be anticipated. Therefore, it is necessary to have an early warning system for flooding so that people can anticipate the situation. This flood warning system will work automatically periodically to find out the water level in the environment around the house. In this prototype the flood level monitoring system utilizes a water level sensor based on the nodemcu 8266 micro controller and a WhatsApp message as a notification to homeowners when the water level is at certain levels can anticipate flooding.